Views regarding the provision of prehospital critical care in the UK. Issue 5 (22nd April 2009) - Mackenzie, R; Steel, A; French, J; Wharton, R; Lewis, S; Bates, A; Daniels, T; Rosenfeld, M
Abstract : Aims: There is a lack of consensus regarding the role for critical care in the prehospital environment in the UK. It was hypothesised that this related to differences in views and understanding among opinion leaders within influential prehospital care organisations. Methods: A 38-item survey was developed by an established paramedic-physician prehospital critical care service. The survey was distributed to individuals in senior positions within seven organisations that have a major influence on UK prehospital services. Analysis comprised a description of the distribution of results, assessment of the level of agreement with each statement by professional background and current involvement in prehospital critical care and evaluation of the overall consistency of responses. Free-text comments were invited to illustrate the reasoning behind each response. Results: There were 32 respondents. The estimated response rate was 40%. The consistency of the questionnaire responses was very high. Overall, all individuals agreed with most of the statements. Paramedic respondents were more likely to disagree with statements that suggested that critical care involved interventions that exceed the current capability of the NHS ambulance service (p<0.05). Free-text comments revealed wide differences of opinion. Conclusion: Although there appears to be broad agreement among opinion leaders regarding the concepts underpinning existing prehospital critical care services, areas of contention are highlighted that may help explain the current lack of consensus. Cooperative efforts to assess the current demand and clinical evidence would assist in the creation of a joint consensus and allow effective future planning for the provision of prehospital critical care throughout the UK.